Self-Healing untuk Mengurangi Stres Akademik Mahasiswa saat Kuliah Daring - Anna Aisa; Iswa Hasanah; Uswatun Hasanah; Sri Rizqi Wahyuningrum (Program Studi BKPI IAIN Salatiga, 2021)
The impact caused by the Covid-19 pandemic in the world of education in Indonesia is the changing pattern of lectures. Lecture activities that were originally face-to-face must switch to online lectures. This changing pattern of lecture approach triggers the emergence of academic stress in students. High academic stress can affect the mental and physical condition of students which has an impact on decreasing academic ability. One way to reduce student academic stress is self-healing. This study aims to figure out the contribution of self-healing in reducing student academic stress towards online lectures during the Covid-19 pandemic. This study is a qualitative research with descriptive type. Five subjects students of IAIN Madura were obtained by purposive method. Data were collected through interviews with the subjects and analyzed by the data explication method. The results showed that all five subjects experienced a decrease in academic stress levels after self-healing. For physical changes, the five subjects no longer feel weak, the body is getting healthier and not easily tired. Meanwhile, mentally, the five subjects were ready and responsive in participating the following online lectures, enthusiastic about doing the assignments given by the lecturer and keen to ask questions and find out any information on their own about learning materials and something that had not been understood yet. Besides self-healing, online learning needs to be supported by facilities and infrastructure, readiness and skills of lecturers so that academic stress on students can be avoided.